Post-legislative Scrutiny (PLS) in the Process of Democratic Transition in Malaysia - Khoo Ying Hooi (Jember University Press, 2020)
Malaysia’s 14th general election in 2018 saw the fall of the Barisan Nasional (BN) regime after ruling the country for more than six decades. Prior to the election, Malaysia faced challenges ranging from the absence of state legitimacy, fragile institutions to corruption scandals, leaving little room to have robust discourse on legislative reforms. Promise 16 of the Pakatan Harapan (PH) election manifesto prior to the election, pledges to restore the dignity of Parliament to institutionalize the select committee system in Parliament and the Senate to enable them to function effectively. Whilst there is limited post-legislative scrutiny (PLS) in Malaysia for now, the various reforms in the phase of democratic transition to the administration of PH is a positive sign of the possibility for Malaysia to move into better law-making procedures. This paper examines the work that is currently being undertaken in the Parliament of Malaysia to assess whether the current parliamentary reforms can pave the way for the PLS mechanism to be put in place.